2004
DOI: 10.1021/ja047272c
|View full text |Cite
|
Sign up to set email alerts
|

Selective Tryptophan Modification with Rhodium Carbenoids in Aqueous Solution

Abstract: A new transition metal-based reaction has been developed for the selective modification of tryptophan residues on protein substrates. After activation of vinyl-substituted diazo compounds by Rh2(OAc)4, the resulting metallocarbenoid intermediates were found to modify indoles in aqueous media despite competing reactions with water. Both N- and 2-substituted indole products were observed in the reaction. Following initial small-molecule studies, the reaction was performed on two protein substrates. Both myoglobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
199
0
16

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(220 citation statements)
references
References 12 publications
5
199
0
16
Order By: Relevance
“…A further example of intriguing TM catalysis was first reported by Antos and Francis 136 , utilising rhodium-generated carbenoids formed from diazo reagents for modification of tryptophan residues. While this reaction initially required quite harsh acidic conditions (pH 3), it was subsequently found that this was primarily to denature early protein substrates and hence to expose the reactive tryptophan residue; conjugations at pH 6 are now possible 137 .…”
Section: Review Nature Communications | Doi: 101038/ncomms5740mentioning
confidence: 99%
“…A further example of intriguing TM catalysis was first reported by Antos and Francis 136 , utilising rhodium-generated carbenoids formed from diazo reagents for modification of tryptophan residues. While this reaction initially required quite harsh acidic conditions (pH 3), it was subsequently found that this was primarily to denature early protein substrates and hence to expose the reactive tryptophan residue; conjugations at pH 6 are now possible 137 .…”
Section: Review Nature Communications | Doi: 101038/ncomms5740mentioning
confidence: 99%
“…There was established reactivity of these complexes toward tryptophan side chains [6], and we developed robust, general, and reliable methods for the synthesis and purification of rhodium(II) metallopeptides [7][8][9]. The metalation of unprotected peptides did not affect folding, and could even be used to enforce helical structure [7].…”
Section: Resultsmentioning
confidence: 99%
“…[255] 185 kann eine elektrophile aromatische Substitution an einem Tyr in einem Protein 186 eingehen und zu einer kovalenten Bindung in 187 führen. Diese Konjugation, die auch Trp-Aminosäuren in Proteinen funktionalisieren kann, [256,257] wurde auf die Verankerung von Peptidbindungsmarkern, insbesondere von FLAG-Epitopen [258] und LBTs, [246] an das Protein Chymotrypsinogen verwendet. Im Allgemeinen wurden Umsätze bis 84 % bei Peptiden mit mehreren Gly-Aminosäuren am Anilinmarker erzielt, was auf die notwendige Voraussetzung einer flexiblen Region für die Tyr-Funktionalisierung hinweist.…”
Section: Mannich-peptidkonjugation An Tyrosine In Proteinenunclassified